Shared Book Reading Interventions With English Learners: A Meta-Analysis. (October 2018) - Fitton, Lisa; McIlraith, Autumn L.; Wood, Carla L.
The present meta-analysis was conducted to examine how shared book reading affects the English language and literacy skills of young children learning English as a second language. The final analysis included 54 studies of shared reading conducted in the United States. Features of the intervention and child characteristics were tested as potential moderators, and the impact of methodological criteria was examined using sensitivity analyses. Results revealed an overall significant, positive effect of shared reading on English learners' outcomes. Children's developmental status moderated this effect, with larger effect sizes found in studies including only typically developing participants than in studies including only participants with developmental disorders. No other significant moderators were identified. The main positive effect was robust to the application of more stringent methodological inclusion criteria. These results support shared book reading as an early educational activity for young English learners.